2012
DOI: 10.3727/096368912x640448
|View full text |Cite
|
Sign up to set email alerts
|

Intraparenchymal Injection of Bone Marrow Mesenchymal Stem Cells Reduces Kidney Fibrosis after Ischemia-Reperfusion in Cyclosporine-Immunosuppressed Rats

Abstract: Ischemia-reperfusion and immunosuppressive therapy are a major cause of progressive renal failure after kidney transplantation. Recent studies have shown that administration of bone marrow mesenchymal stem cells (MSCs) improves kidney functional recovery in the acute phase of post ischemia-reperfusion injury. In the present study, we used an original model of renal ischemia-reperfusion in immunosuppressed rats (NIRC) to investigate the effects of bone marrow MSCs on progression of chronic renal failure and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 46 publications
(54 reference statements)
3
65
0
2
Order By: Relevance
“…In rodent models, MSCs retard the progression of CKD by suppressing fibrosis. [37][38][39] Our study confirmed this effect and further demonstrated that MSC therapy with CS-IGF-1C hydrogel showed increased attenuation of fibrosis by substantially inhibiting expression of MMPs; this has been implicated in initiation and progression of renal fibrosis through epithelialmesenchymal transition as well as activation of fibroblasts. 40 Concordantly, cotransplantation of ADSCs and CS-IGF-1C hydrogel led to downregulated expression of a range of profibrotic genes, such as TGF-b, collagen type 1 a1, and fibronectin, in addition to increased expression of antifibrotic genes after AKI.…”
Section: Discussionsupporting
confidence: 75%
“…In rodent models, MSCs retard the progression of CKD by suppressing fibrosis. [37][38][39] Our study confirmed this effect and further demonstrated that MSC therapy with CS-IGF-1C hydrogel showed increased attenuation of fibrosis by substantially inhibiting expression of MMPs; this has been implicated in initiation and progression of renal fibrosis through epithelialmesenchymal transition as well as activation of fibroblasts. 40 Concordantly, cotransplantation of ADSCs and CS-IGF-1C hydrogel led to downregulated expression of a range of profibrotic genes, such as TGF-b, collagen type 1 a1, and fibronectin, in addition to increased expression of antifibrotic genes after AKI.…”
Section: Discussionsupporting
confidence: 75%
“…19 Furthermore, several animal studies determined that the administration of mesenchymal-derived stem cells significantly reduced fibrosis in the lung, kidney, and liver. [12][13][14] There are, however, no reports of stem cell-based therapy in the clinical management of urethral stricture disease. Our study is a proofof-concept study that demonstrates that local injection of ADSCs prevents fibrosis induced by TGF-β1 injection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, a number of animal studies have demonstrated that mesenchymal stem cells have antifibrotic properties that can reduce fibrosis in the lung, kidney, and liver. [12][13][14] We sought to evaluate the potential therapeutic benefits of adipose-derived stem cell (ADSCs) therapy in decreasing fibrotic tissue in a rat model of urethral fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Direct parenchymal injection allows efficient local delivery of MSCs and promotes the recovery of renal fuction. 29 However, the locally delivered MSCs tend to be confined to the injection site without diffusion to the whole kidney. Furthermore, this invasive method may cause bleeding and tissue destruction leading to secondary kidney damage and adverse effect on renal function recovery.…”
Section: Discussionmentioning
confidence: 99%